Concept and Scope of Academic Supervision Case Study: Implementation of Academic Supervision - Maharani, Dewa Ayu Nita; Mandabayan, Reni; Purnami, Putu Okta; Putra, Anak Agung Pinta Dwi; Astari, Ni Luh Putu Dian; Amarawati, Diah; Werang, Basilius Redan (PT FORMOSA CENDEKIA GLOBAL, 2025)
In order to ascertain the degree to which the implementation of supervision can enhance the caliber of instruction and foster teacher professionalism, this study intends to investigate the idea and application of academic supervision as well as its application within the framework of a case study in a school. By gathering literature (related materials) from books, journals, and other sources pertaining to the subject of educational administration and supervision, this article employs a literature study methodology. When it is thought that there is enough study material, it is thoroughly explored and examined, and the author then attempts to draw fresh conclusions from the analysis of the data. We refer to this approach as the Systematic Literature Review (SLR) method.